LEGALITAS WISATA RUANG ANGKASA DAN PERLINDUNGAN WISATAWAN RUANG ANGKASA DITINJAU DARI HUKUM INTERNASIONAL - Rieder Anggiat Natanael Sihombing (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2021)
The regulation of space tourism and whether the position of a space tourist has the same position as an astronaut who is a human ambassador in space, especially the gap between the fact that space tourism activities are becoming more realistic and international law rules that have not yet regulated space tourism activities. in particular. This research uses literature study method with secondary research materials. Space tourism as a result of technological developments in the use of space activities is accommodated by the 1967 Space Treaty as the basis of international law regarding outer space. The presence of tourists in tourism activities is inseparable, their presence is protected by the Space Treaty 1967, the Liability Convention 1972, and the Registration Convention 1975. The occurrence of space tourism certainly requires the latest international legal products to become regulations related to space tourism activities, the need for a new international agreement that regulates space activities so that these activities have a concrete legal basis so that they do not cause problems from a regulatory perspective.